Pengaruh Model Guided Discovery Learning Terhadap Literasi Sains ditinjau dari Kecerdasan Naturalis - Khasanah, Nur; Dwiastuti, Sri; Nurmiyati, Nurmiyati (Universitas Sebelas Maret, 2016)
This study was aimed to know: (1) the influence of guided discovery learning model to the scientific literacy; (2) the influence of naturalist intelligence to the scientific literacy; (3) the interaction between learning model and naturalist intelligence to the scientific literacy. This study is a quasy experimental research with 2x3 factorial design. The popullation of this study is all of students grade X SMA N 1 Ngemplak academic year 2015/2016. Sample of class is selected by purpossive sampling technique. Data is collected by test techniques (Instrument matter of Nature of Science Literacy Test/NOSLiT) and non-test technique (quesionnaire, observation, and documentation). The data is analyzed by Two Ways analysis of variance test with different content of cell with level of significance 5%. Data analyzing is helped by Statistical Product and Service Solution (SPSS) program 21 version. The results showed that there was the influence of the use of guided discovery learning models to scientific literacy (Sig. = 0.047) <α = 0.05. There was the influence of naturalist intelligence toward scientific literacy (Sig. = 0.015) <α = 0.05, and there was no effect interaction between learning-models and naturalist towards their scientific literacy (Sig. = 0,544)>α = 0.05.Keywords: Guided Discovery Learning Model, Scientific Literacy, Naturalist Intelligence